Edukasi Peran Fisioterapi Upaya Mengurangi Nyeri pada Kasus Low Back Pain terhadap Petani di Dusun Bulakrejo Kabupaten Ngawi - Dewi Hapsari; Sri Sunaringsih Ika Wardojo (Lembaga Pengembangan Kinerja Dosen, 2025)
Low back pain is a discomforting condition that can cause various disorders and potentially disrupt a person's quality of life, such as causing decreased work productivity. Therefore, it is important for the community, especially farmers in Bulakrejo Hamlet, Ngawi Regency. To improve understanding of low back pain, efforts are needed to expand farmers' knowledge regarding this condition, including its definition, prevention, and treatment in Bulakrejo Hamlet. The method applied was providing physiotherapy education through health promotion about low back pain using leaflets as a medium for information delivery. A question and answer session was also conducted to measure the level of understanding of farmers in Bulakrejo Hamlet and provide exercises that can address problems of weakness, stiffness, limitations and pain in the back muscles. The activity ran smoothly and the material was easily understood by farmers in Bulakrejo Hamlet. Evaluation results showed an increase in farmers' knowledge, from 40% to 90%. The extension activity proved effective in increasing farmers' understanding of low back pain cases.